Given f ( x ) = x2 - 2 x + 8 and g( x ) = √(x+ 6) evaluate f (3) and g(3)
Okay we've two function evaluations to do here and we've also obtained two functions so we're going to decide which function to employ for the evaluations. Here the key is to notice the letter that is in front of the parenthesis. For f(3) we will use the function f( x ) and for
g (3) .we will employ g ( x ) . In other terms, we just have to make sure that the variables match up.
Following are the evaluations for this part.
f(3) = (3)2 - 2 (3) +8 = 9 - 6 + 8 = 11
g(3) =√(3+6) =√9=3